Prospecção de regiões pleiotrópicas para características complexas relevantes ao melhoramento bovino a partir de GWAS bi-característica - Buss, Carlos Eduardo (2019)
The demand for sustainable beef production systems drives the development of new tools that aim to reduce the production costs and to avoid losses in meat quality. The objective of this study was to identify possible interactions among meat quality, calcium (Ca2+) content and feed efficiency, as well as to investigate which biological mechanisms underlie Nelore's complex traits modulation. For this, we estimated heritability, genetic correlations, and bivariate Genome Wide Association Study (GWAS). Our results indicated that the efficient animal's selection (low RFI) may not necessarily generate animals with less subcutaneous fat deposition, but may increase intramuscular fat (IMF). We identified a region located on chromosome 20, close to the genes CD180 and MAST4, both related to the regulation of lipid metabolism. IMF showed no correlation with other fat deposits in our data, indicating this trait could be selected independently from the others for breeding purposes. In the second chapter, we analyzed the influence of Ca2+ on meat tenderness measured at 14 days after slaughter (WSF14), and we estimated a negative correlation between these traits, which evidences a low shear force indices (tender beef) are associated with high Ca2+ content index. These associations may be the effect of calcium-dependent proteases on meat tenderness. From an integrative Transcriptome-wide association study (TWAS) approach, combining bivariate GWAS and cis-eQTL (SMR), we identified two candidate genes (DAP3 and ALKBH3) regulators of apoptosis, essential for the muscle-to-meat conversion process. Thus, the approaches allowed to estimate the association of complex phenotypes relevant to bovine breeding, as well as to indicate new candidate genes and metabolic pathways, decomposing part of the additive variance of these traits, contributing toward new strategies on genomic selection.